Pregnant patient with Xp11.2/transcription factor E3 translocation renal cell carcinoma: a case report and literature review - Wang, Yanchen; Guo, Xiaoyan; Meng, Zhe; Cui, Yong; Sun, Yaofei (Frontiers in Oncology, 2024)
MiT family translocation renal cell carcinomas primarily include Xp11.2/transcription factor E3 (TFE3) gene fusion-associated renal cell carcinoma(Xp11.2 tRCC) and t(6;11)/TFEB gene fusionassociated RCC. Clinical cases of these carcinomas are rare. Fluorescence in situ hybridization can be used to identify the type, but these are no standard diagnostic and treatment methods available, and the prognosis remains controversial. Herein, we present a case of a patient with Xp11.2 tRCC at 29 weeks of gestation. The baby was successfully delivered, and radical surgery was performed for renal cancer at the same time. This is a unique and extremely rare case. We have described the case and performed a literature review to report the progress of current research on the treatment and prognosis of pregnant patients with Xp11.2/TFE3 translocation renal cell carcinoma. This study aims to contribute to improving the diagnosis and treatment of Xp11.2 tRCC in pregnant patients.